Research note: Interactive influence of phytate-phosphorus and phytase on calcium utilization in broiler chickens fed potato protein-based basal diets - O.T. Osunbami; O. Adeola (Poultry Science)
Through formation of calcium-phytate chelates, dietary phytate-P (PP) can influence the extra-phosphoric effects of phytase on calcium (Ca) utilization. Calcium utilization changes in the absence or presence of PP and without or with added phytase in broiler chicken diets were investigated in a study that used 320 male broiler chickens and offered experimental diets based on potato protein concentrate from d 18 to 21 post hatching. Diets were nutrient-adequate positive control (4.8 g non-PP/kg; 0 g PP/kg) and 2 nutrient-reduced (2.8 g non-PP/kg) containing either 0 or 4.4 g PP/kg solely from rice bran and added phytase at 0 or 4,000 FYT/kg in a 1 + 2 × 2 factorial. The body weight gain, feed intake, and gain-to-feed ratio of birds fed the 4.8 g non-PP/kg containing 0 g PP/kg diet were not different from those fed the 2.8 g non-PP/kg containing 0 g PP/kg diet, but lower (P < 0.001) than birds fed the 2.8 g non-PP/kg containing 4.4 g PP/kg diet despite the higher (4.8 g) non-phytate phosphorus content. This outcome was consistent regardless of phytase supplementation and may be attributed to the equivalent potato protein concentrate levels in both the positive control and 0 g PP/kg diets. Phytate-P reduced (P < 0.001) apparent ileal digestibility (AID) and apparent total tract retention (ATTR) of Ca and P. Phytase supplementation improved the AID and ATTR of P in 4.4 g PP/kg but not in 0 g PP/kg diet due to a lack of the substrate PP, which resulted in a PP by phytase interaction (P < 0.001). Furthermore, added phytase increased ATTR of Ca by a greater magnitude (25.1 percentage points) in the 4.4 g PP/kg diet than (8.5 percentage points) in the 0 g PP/kg diet, resulting in a significant interaction (P < 0.05). Therefore, the results suggest that the enhanced Ca utilization observed with a high phytase dose may not be solely attributed to the Ca released from phytate breakdown but may involve additional mechanisms influencing Ca retention. Additionally, the efficacy of phytase in ameliorating the antinutritive effect of phytate on Ca and P utilization was further substantiated.